Jurisprudence as a Zone of Reflection on Cultural Diversity: Juridical Appropriation of Cultural Notions - Vera Lugo, Juan Pablo; Universidad Javeriana, Departamento de Antropologia (Editorial Pontificia Universidad Javeriana, 2006)
The emergence of cultural diversity rhetoric has promoted the incorporation of those rights vindicated by multiple social movements during the 60’s, 70’s and 80’s into the field of transnational law. Different social groups have demanded recognition of their singularity and the establishment of their rights alongside those of majoritarian societies. In the Colombian legal arena, this demand has been developed particularly through the work of the country’s Constitutional Court since the early 90’s. This article explores the way in which cultural diversity has been incorporated into legal discourse, and specifically the way in which the rationalization of the concept has operated. The document presents useful elements for understanding how this field of law has produced certain affects on Colombian cultural diversity as well as on the values that have been formalized through the Court’s rulings. Three legal concepts that emerge out of the need to articulate law to the characteristics proper of indigenous cultural difference are identified. These are: collective property, collective subject and territorial sphere. Finally, the article shows how these categories correspond to imaginaries and believes that have traditionally dominated a vision of indigenous cultural difference founded in radical “othership”, exotism and cultural essentialism.